THE FIVE COMMANDMENTS TO YOUNG AND ADULT EDUCATION TEACHERS: IDENTITIES AND REPRESENTATIONS OF THE DESIRED TEACH-ER IN A NEWSPAPER REPORT - Dias Magalhães, Mônica Trindade; Biavati, Nádia Dolores Fernandes (fólio - revista de letras, 2020)
The present work makes an analysis of a newspaper report entitled ‘The five commandments to the young and adult education teachers’, published on March 28th 2019 on the website of the magazine ‘Gestão Escolar (Nova Escola)’ . The analysis was based on the theoretical and methodological frameworks of Social Representation Theory, by Moscovici (2009) and Jodelet (2011) and Enunciation Semantics Theory, by Dias (2013) and Guimarães (2017, 2018), whose concept of speaker and enunciator were adopted in this paper. The concepts of culture, proposed by Carmo (2014); identity, proposed by Hall (2011), Coracini (2003) and Bauman (2005); and cultural diversity, proposed by Cox (1993), were also used in order to identify and analyze the social representations and identities that permeate the discourses in the newspaper report. The conclusion is that the representations of young and adult education teachers outline how the student should be regarded, beyond the contents and skills demanded from them.